Secretary [videorecording (DVD)] - Shainberg, Steven, 1963-; Spader, James; Gyllenhaal, Maggie, 1977-; Gaitskill, Mary, 1954- (Distributed by Lions Gate Entertainment, 2008)
Lee has a few strikes against her when she applies for a secretarial position at the law office of E. Edward Grey. In between typing, filing and coffee making, Lee and Mr. Grey embark on a personal relationship together, crossing the line.